2023
DOI: 10.3390/jmse11061208
|View full text |Cite
|
Sign up to set email alerts
|

Towards Multi-AUV Collaboration and Coordination: A Gesture-Based Multi-AUV Hierarchical Language and a Language Framework Comparison System

Abstract: The underwater environment is a harmful environment, yet one of the richest and least exploited. For these reasons the idea of a robotic companion with the task of supporting and monitoring divers during their activities and operations has been proposed. However, the idea of a platoon of robots at the diver’s disposal has never been fully addressed in these proposals due to the high cost of implementation and the usability, weight and bulk of the robots. Nevertheless, recent advancements in swarm robotics, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Zhang et al [15] introduced an AUV cluster network navigation accuracy analysis method based on the Fisher information matrix and demonstrated that using the information on the entire formation when estimating the position of the following AUV could improve the positioning accuracy of the following AUV. Chiarella D. [16] designed a multi-AUV framework, defining a hierarchical work order of AUVs to efficiently complete cooperative tasks, and proposed a gesture-based UHRI framework to optimize coordination and communication between AUVs while supporting the other communication methods.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [15] introduced an AUV cluster network navigation accuracy analysis method based on the Fisher information matrix and demonstrated that using the information on the entire formation when estimating the position of the following AUV could improve the positioning accuracy of the following AUV. Chiarella D. [16] designed a multi-AUV framework, defining a hierarchical work order of AUVs to efficiently complete cooperative tasks, and proposed a gesture-based UHRI framework to optimize coordination and communication between AUVs while supporting the other communication methods.…”
Section: Introductionmentioning
confidence: 99%